Cyrus the Great: The Persian king in the context of world history - E.A. Tchiglintsev; E.V. Rung (Ученые записки Казанского университета: Серия Гуманитарные науки)
The paper is devoted to the study of the life and activities of the Persian king Cyrus the Great, as well as the transformation of his image in the socio-cultural and political practices of subsequent eras. Herodotus tells the earliest version of the life of Cyrus. He pays attention to the “legend of Cyrus”, which included the tradition of the origin and death of this king. In fact, he knows several versions of Cyrus' legend, later reflected in the Persian History of Ctesias of Cnidus and in Xenophon's Cyropaedia. Meanwhile, there is no Oriental, including Old-Persian, evidence attesting of the perception of Cyrus by his subjects or his self-representation. The famous Cyrus Cylinder was not such evidence, but rather a reflection of the propaganda intended for conquered peoples, which was associated with a specific event – the capture of Cyrus of Babylon in 539 BC. However, the Cyrus Cylinder became the basis for a completely “new legend of Cyrus”, which was circulated in the second half of the 20th century and represents the transformation of this image in contemporary political culture. The conclusion has been made that the legend of Cyrus, which developed in antiquity, was supplemented in the 20th century with the “new legend of Cyrus”, which represents him as the recognized forerunner in the world community of modern ideological, political, and legal rules in the field of human rights. Thus, Cyrus the Great, legendary in antiquity and ultimately mythologized in new and modern times, became one of the few ancient rulers who continue to actively “participate” in the modern intellectual, cultural and political space, experiencing metamorphosis and undergoing transformation.